â€˜BRCA1’ RESPONSIVENESS TOWARDS BREAST CANCER-A POPULATION-WISE PHARMACOGENOMIC ANALYSIS - Iyer, Preethi M.; P., Sanjay Kumar; S., Karthikeyan; Namboori, P. K. Krishnan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: In the present pharmacogenomic work, the genetic, epigenetic and environmental factors associated with BRCA1 induced breast cancer, cancer proneness and its variants across different populations like Indian, Netherland, Belgium, Denmark, Austrian, New Zealand, Sweden, Malaysian and Norwegian and the â€˜mutation and methylation-prone' region of BRCA1 have been computed. Methods: The global variations associated with the disease have been identified from the â€˜Leiden open variation database (LOVD 3.0)' and â€˜Indian genome variation database (IGVDB)'. The variants, â€˜single nucleotide polymorphisms (SNPs)' are then characterized. The epigenetic factors associated with breast cancer have been identified from the clinical reports and further scrutinized using EpiGRAPH tool. The various contributing environmental factors responsible for the variations have been considered. Results: All the variants across different populations such as Indian, Netherland, Belgium, Denmark, Austrian, New Zealand, Sweden, Malaysian and Norwegian are found to be in a specific transcript of BRCA1 that ranges within 41,196,312-41,277,500 (81,189 base pairs) of the chromosome 17. Two â€˜single nucleotide variations (SNVs)' (5266dupC: rs397507246 and 68_69delAG: rs386833395) have been identified as risk factors in hereditary breast and ovarian cancer syndrome in the global population and 39 SNPs have been identified as pathogenic and deleterious. â€˜Evolutionary history' seems to be the most significant attribute in the predictability of methylation of BRCA1. Unhealthy dietary habits, obesity, use of unsafe cosmetics, estrogen exposure, â€˜hormone replacement therapy (HRT)', use of oral contraceptives and smoking are the major environmental risk factors associated with breast cancer incidence. Conclusion: This chromosome location (41,196,312-41,277,500 (81,189 base pairs)) can be considered as the population-specific sensitive region corresponding to BRCA1 mutation. This supports the fact that stabilization within the region can be a promising technique to control the epigenetic variants associated with the global position. The global variation in the proneness of the disease may be due to a cumulative effect of genetic, epigenetic and environmental factors subject to further experimentations with identical variations and populations.Â